Bibliometric Analysis of Research on Enabling School Structures: A Scientific Mapping of the Literature from 2001 to 2023 - Özel, Sezai; Zincirli, Muhammed (Atatürk Üniversitesi, 2026)
The present study offers a bibliometric analysis of academic research concerning the enabling school structures. The study drew data from the Scopus database, identifying 298 publications spanning a 23-year period. In order to maintain analytical consistency and avoid distortions since 2024 was going on at the time of the research, 34 publications from that year were excluded, thereby narrowing the dataset to 264 items. The bibliometric mapping and data visualisation were performed using VOSviewer software. The publications were examined according to various criteria, including publication year, annual citation counts, publication type, country of origin, affiliated institutions, most-cited sources and authors, and keyword distribution. A salient finding of the study is the predominance of journal articles, which account for 220 entries, constituting approximately 83.3% of the total literature. With respect to national contributions, the United States is the leading nation, having published 101 scholarly works. Furthermore, the United States has distinguished itself through its robust international research collaborations. Co-citation analysis revealed Wayne K. Hoy as the most influential scholar in the field, with a total of 1,034 citations. At the institutional level, William & Mary University was the most prolific contributor, with a total of 12 publications. This study provides a comprehensive overview of the intellectual structure and publication trends related to enabling school structures. By highlighting key contributors, institutional affiliations, and evolving research patterns, it provides valuable insights for scholars and policymakers and is expected to guide future research in this domain.

Bu çalışma, kolaylaştırıcı okul yapıları ile ilgili akademik araştırmaların bibliyometrik analizini sunmaktadır. Çalışma, Scopus veritabanından elde edilen verileri kullanarak 23 yıllık bir dönemi kapsayan 298 yayını belirlemiştir. Analitik tutarlılığı korumak ve araştırma sırasında 2024 yılı devam ettiği için çarpıtmaları önlemek amacıyla, o yıla ait 34 yayın hariç tutulmuş ve böylece veri seti 264 öğeye indirgenmiştir. Bibliyometrik haritalama ve veri görselleştirme, VOSviewer yazılımı kullanılarak gerçekleştirilmiştir. Yayınlar, yayın yılı, yıllık atıf sayısı, yayın türü, menşe ülke, bağlı kurumlar, en çok atıf alan kaynaklar ve yazarlar ve anahtar kelime dağılımı gibi çeşitli kriterlere göre incelenmiştir. Çalışmanın öne çıkan bir bulgusu, toplam literatürün yaklaşık %83,3'ünü oluşturan 220 giriş ile dergi makalelerinin baskınlığıdır. Ulusal katkılar açısından, 101 akademik çalışma yayınlayan Amerika Birleşik Devletleri lider konumdadır. Ayrıca, Amerika Birleşik Devletleri, güçlü uluslararası araştırma işbirlikleriyle de öne çıkmaktadır. Ortak atıf analizi, Wayne K. Hoy'un toplam 1.034 atıfla bu alandaki en etkili akademisyen olduğunu ortaya koymuştur. Kurumsal düzeyde, William & Mary Üniversitesi toplam 12 yayınla en verimli katkı sağlayan kurum olmuştur. Bu çalışma, okul yapılarının etkinleştirilmesiyle ilgili entelektüel yapı ve yayın eğilimlerine kapsamlı bir genel bakış sunmaktadır. Önemli katkı sağlayanları, kurumsal bağlantıları ve gelişen araştırma modellerini vurgulayarak, akademisyenler ve politika yapıcılar için değerli bilgiler sağlar ve bu alandaki gelecekteki araştırmalara rehberlik etmesi beklenmektedir.
Kolaylaştırıcı Okul Yapısı Üzerine Yapılan Araştırmaların Bibliyometrik İncelemesi: Literatürün Bilim Haritalaması, 2001’den 2023’e
Keywords: Education Management; Eğitim Yönetimi